2019
DOI: 10.1080/03075079.2019.1610865
|View full text |Cite
|
Sign up to set email alerts
|

Developing learning relationships in intercultural and multi-disciplinary environments: a mixed method investigation of management students’ experiences

Abstract: Developing learning relationships in intercultural and multidisciplinary environments: A mixed method investigation of management students' experiences. Studies in Higher Education. Developing learning relationships in intercultural and multidisciplinary environments: A mixed method investigation of management students' experiences

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 32 publications
(74 reference statements)
0
18
0
Order By: Relevance
“…On the one hand, previous results have found empirical evidence in university contexts of the presence of various proximity factors linked to social, cultural, geographical, academic and personal aspects that favour the formation of links between students. On the other hand, although learning and work relations, as well as inter- and inter-group learning relations in academic relationship-based settings have received notable attention in the literature, for example, in Australia (Neri & Ville, 2008 ), Spain (Hernandez-Nanclares et al, 2017 ; Tomás-Miquel et al, 2016 ), The Netherlands (Hommes et al, 2012 ; Hommes et al, 2014 ) and the UK (Héliot et al, 2020 ; Rienties & Héliot, 2018 ; Rienties & Tempelaar, 2018 ), specific studies on homophily or proximity factors in these contexts are still scarce, thus requiring further attention.…”
Section: Theoretical Background and Research Questionsmentioning
confidence: 99%
“…On the one hand, previous results have found empirical evidence in university contexts of the presence of various proximity factors linked to social, cultural, geographical, academic and personal aspects that favour the formation of links between students. On the other hand, although learning and work relations, as well as inter- and inter-group learning relations in academic relationship-based settings have received notable attention in the literature, for example, in Australia (Neri & Ville, 2008 ), Spain (Hernandez-Nanclares et al, 2017 ; Tomás-Miquel et al, 2016 ), The Netherlands (Hommes et al, 2012 ; Hommes et al, 2014 ) and the UK (Héliot et al, 2020 ; Rienties & Héliot, 2018 ; Rienties & Tempelaar, 2018 ), specific studies on homophily or proximity factors in these contexts are still scarce, thus requiring further attention.…”
Section: Theoretical Background and Research Questionsmentioning
confidence: 99%
“…The findings of the interviews did indicate that the learning design decisions in Course A helped learners to start to interact with other learners, however, relatively few learners were able to build cross-cultural learning links. This indicates a need for teacher's intervention to consider learning relationships in intercultural and multi-disciplinary environments e.g., allocate students from different cultural backgrounds and create opportunities for cross cultural interactions (Héliot et al, 2020;Leask, 2009), and reduce intergroup prejudice (Allport, 1954), hence increasing students' comfort zone in culture and social interactions. This need to reconsider the learning design was also illustrated by the negative E-I index, whereby more relations were maintained with learners with the same GLOBE background.…”
Section: Discussionmentioning
confidence: 99%
“…For example, research using social identity theory combining SNA analysis of 113 postgraduate management students in one UK business school with follow-up focus group interviews of 16 students showed that nearly all international students "shared experiences of perceived discrimination when interacting with out-group members" (Rienties & Héliot, 2018). The triangulation of data showed that the type and ways in which discrimination was experienced differed substantially depending on the relative social network position an international student held, and the type of relations that they formed (Héliot et al, 2020).…”
Section: Creating Inclusive Learning Designs That Build Student Learn...mentioning
confidence: 99%
“…Several studies (e.g., Law et al, 2007; Martınez et al, 2003; Rienties & Hosein, 2015; Thomas et al, 2019)—combining mixed approaches for analysing education networks—were conducted. However, studies (e.g., Héliot et al, 2020; de Laat et al, 2007) dedicated to student networks together with student performance and using mixed SNA methods are rare and could be considered and employed more (Edwards, 2010). For instance, in order to analyse and understand the patterns of participant interactions within a CSCL context, de Laat et al (2007) combined several techniques: (1) from SNA; (2) from content analysis (CA); and (3) from critical event recall (CER).…”
Section: Discussionmentioning
confidence: 99%